TCR Signaling Abnormalities in Human Th2-Associated Atopic Disease - Milner, Joshua D. (Frontiers in Immunology, 2018)
Stimulation of naïve CD4 T cells with weak T cell receptor agonists even in the absence of T helper-skewing cytokines can result in IL-4 production which can drive a Th2 response. Evidence for the in vivo consequences of such a phenomenon can be found in a number of mouse models and, importantly, a series of monogenic human diseases associated with significant atopy which are caused by mutations in the T cell receptor signaling cascade. Such diseases can help understand how Th2 responses evolve in humans, and potentially provide insight into therapeutic interventions.